Gel-Free Tools for Quick and Simple Screening of Anti-Topoisomerase 1 Compounds - Josephine Geertsen Keller; Kamilla Vandsø Petersen; Karol Mizielinski; Celine Thiesen; Lotte Bjergbæk; Rosa M. Reguera; Yolanda Pérez-Pertejo; Rafael Balaña-Fouce; Angela Trejo; Carme Masdeu; Concepcion Alonso; Birgitta R. Knudsen; et al. (MDPI AG, 2023)
With the increasing need for effective compounds against cancer or pathogen-borne diseases, the development of new tools to investigate the enzymatic activity of biomarkers is necessary. Among these biomarkers are DNA topoisomerases, which are key enzymes that modify DNA and regulate DNA topology during cellular processes. Over the years, libraries of natural and synthetic small-molecule compounds have been extensively investigated as potential anti-cancer, anti-bacterial, or anti-parasitic drugs targeting topoisomerases. However, the current tools for measuring the potential inhibition of topoisomerase activity are time consuming and not easily adaptable outside specialized laboratories. Here, we present rolling circle amplification-based methods that provide fast and easy readouts for screening of compounds against type 1 topoisomerases. Specific assays for the investigation of the potential inhibition of eukaryotic, viral, or bacterial type 1 topoisomerase activity were developed, using human topoisomerase 1, Leishmania donovani topoisomerase 1, monkeypox virus topoisomerase 1, and Mycobacterium smegmatis topoisomerase 1 as model enzymes. The presented tools proved to be sensitive and directly quantitative, paving the way for new diagnostic and drug screening protocols in research and clinical settings.